A look into Calliphora vomitoria after topical treatment with Origanum vulgare essential oil - L. Guidi; E. Grassi; A. Petri; R. Ascrizzi; F. Semprucci; C. Rosati; P. Farina; B. Conti (The European Zoological Journal)
Blowflies like Calliphora vomitoria (Diptera: Calliphoridae) are a notorious nuisance and dangerous mechanical vectors of numerous foodborne pathogens. For these reasons, humans have the necessity to manage them in homes and places visited by people and animals, mainly with indoor and outdoor sprays acting by contact. To reduce the side-effects associated with the overuse of such formulations of synthetic origin, essential oils (EOs) are now proposed as safer and greener botanical alternatives. However, the exact mode(s) of penetration and action of an EO in an insect pest have not yet been exhaustively investigated. In the present work, we first ascertained the toxicity of an Origanum vulgare (Lamiaceae) carvacrol chemotype EO on C. vomitoria adults when applied topically to the thorax. Based on the median lethal dose by direct contact after 24 hours (LD50 = 0.067 µL EO blowfly−1), we then decided to treat other specimens with 0.2 µL EO blowfly−1 to potentially observe thoracic structural and ultrastructural abnormalities through light and transmission electron microscopy (TEM) and possible acetylcholinesterase (AChE) inhibition by Ellman’s colorimetric method performed in vivo. We verified that the EO, showing lipophilic properties, can penetrate the integument, thus causing morphological alterations at the level of the cuticle, epidermis and the underlying muscular and tracheal system, with vacuolization, disorganization and degeneration of the tissues compared to the untreated control. Instead, the AChE activity was not affected by our O. vulgare EO treatment, indicating that this enzyme is not involved in its insecticidal activity.